Early increase of serum ferritin among COVID-19 patients is associated with need of invasive mechanical ventilation and with in-hospital death. Issue 11 (2nd November 2022) - Ramonfaur, Diego; Aguirre-García, Gloria M.; Diaz-Garza, Carlos A.; Torre-Amione, Guillermo; Sanchez-Nava, Victor M.; Lara-Medrano, Reynaldo; Ramírez-Elizondo, María T.; Esparza-Sandoval, Alejandra C.; Ortega-Hernández, Francisco J.; Martínez-Reséndez, Michel F.
Abstract: Background: COVID-19 may trigger an acute hyperinflammatory syndrome characterised by heightened levels of acute phase reactants and is associated with adverse outcomes among hospitalised individuals. The relationship between 48-hour changes in acute phase reactants and adverse outcomes is unclear. This study evaluated the relationship between change in four acute phase reactants (interleukin-6, procalcitonin, ferritin, and C-reactive protein), and the risk for in-hospital death and invasive mechanical ventilation. Methods: A retrospective cohort among 2, 523 adult patients hospitalised with COVID-19 pneumonia was conducted. Changes in IL-6, procalcitonin, ferritin, and CRP from admission to 48 h after admission were recorded. Delta was calculated using the difference in each acute phase reactant at admission and at 48-hours. Delta in acute phase reactants and the risk for in-hospital death and invasive mechanical ventilation was assessed using logistic regression models adjusting for demographics and comorbidities. Results: Patients with both admission and 48-hour measurement for interleukin-6 (IL-6) ( n  = 541), procalcitonin ( n  = 828), ferritin ( n  = 1022), and C-reactive protein (CRP) ( n  = 1919) were included. Baseline characteristics were similar across all four populations. Increases in ferritin associated with a heightened risk of in-hospital death (OR 1.00032; 95%CI 1.00007- 1.00056; p  < .001) and invasive mechanical ventilation (OR 1.00035; 95%CI 1.00014- 1.00055; p  = .001). Therefore, for every 100 ng/mL increase in ferritin, the odds for in-hospital death and invasive mechanical ventilation increase by 3.2% and 3.5%, respectively. Conclusions: Delta in ferritin is associated with in-hospital death and invasive mechanical ventilation. Other acute phase reactants were not associated with these outcomes among COVID-19 inpatients.